KARAKTERISTIK ORGANOLEPTIK PEDA KEMBUNG RENDAH GARAM SELAMA PENGENDALIAN LINGKUNGAN DENGAN PENGGUNAAN KADAR GARAM YANG BERBEDA - Usman Lubis; Evi Liviawaty; Lantun Paradhita Dewanti; Rusky Intan Pratama (Jurnal Perikanan Unram, 2024)
Peda is one of the fermented products made through a spontaneous fermentation process, namely fermentation without starter bacteria. Environmental control is one of the important stages in peda fermentation because at this stage it requires the growth of fermentation bacteria originating from within the fish body. Salt is used during environmental control because salt can inhibit the growth of spoilage microbes and provide a suitable environment for fermentation microbes. The purpose of this study was to determine the use of appropriate salt levels to control the environment for the growth of fermentation bacteria so that the final product produced has uniform quality and the most favorable organoleptic characteristics. This research was conducted in December 2022 at the Fishery Product Processing Laboratory, Faculty of Fisheries and Marine Science, Padjadjaran University. The method used in this research is an experimental method by controlling the fermentation environment for 7 days consisting of six treatments, namely using salt in levels of 0%, 15%, 20%, 25%, 30%, and 35%, with observations made on day 1 to day 7, organoleptic tests were conducted by 15 semi trained panelists. The results of the organoleptic test were analyzed using non-parametric statistics with the Friedman test, if there is a significant difference then a further test of multiple comparison is carried out and the Bayes test is carried out for decision making. The results showed that the best treatment was the treatment using 20% salt content for 7 days with a pH value of 6.3; moisture content of 61.5%; salt content of 11.79% with a median characteristic value of appearance 5, aroma 7, texture 5, and taste 7 which was the most preferred treatment by panelists.